The printmaking bible the complete guide to materials and techniques - D'Arcy Hughes, Ann; Vernon-Morris, Hebe (San Francisco Chronicle Books, 2008)
From the Publisher: Perennially popular, printmaking is enjoying a contemporary resurgence but no comprehensive up-to-date manual on the subject exists. At over 400 pages and packed with 1,000 full-color photos and illustrations, The Printmaking Bible is the definitive resource to the ins-and-outs of every variety of serious printmaking technique practiced today. In-depth instructions are accompanied by profiles that show how working artists create their prints. Historical information, troubleshooting tips, and an extensive resource section provide more invaluable tools. Perfect for students, artists, print aficionados, and collectors, this is truly the ultimate volume for anyone involved in this creative and influential art form.
"Printmaking is a traditional art practice whose creative flexibility keeps it fresh and relevant, popular with each new generation of artists. The Printmaking Bible is the definitive volume on this art form, presenting the tips and tools needed to create great artwork at any level. Including illustrated step-by-step instructions, detailed historical information, troubleshooting tips, an extensive resource section, as well as interviews with working artists, this comprehensive guide is unparalleled in scope and ideal for students and professionals alike." -- Provided by publisher.
Acknowledgments -- Introduction -- 1: Intaglio -- Introduction to intaglio -- Etching -- Metal engraving -- Collagraph -- Printing the intaglio image -- 2: Relief -- Introduction to relief -- Woodcut -- Linocut -- Chine colle -- Wood engraving -- Printing the relief -- 3: Lithography -- Introduction to lithography -- Stone lithography -- Zinc plate lithography -- Polyester plate lithography -- Printing the lithographic image -- 4: Screenprinting -- Introduction to screenprinting -- Equipment and materials -- Stencils -- Printing the screenprint image -- 5: Monotype -- Introduction to monotype -- Color separation -- Additional monotype methods -- 6: Resources -- Workshops -- Workshop listings -- Artist contacts -- Suppliers -- Bibliography -- Glossary -- Index -- Picture credits.
Includes bibliographical references (pages 406-407) and index.
Keywords: Prints -- Technique -- Handbooks, manuals, etc